The design and analysis of an input/output rail-to-rail Op-Amp with class-AB output drive in 55nm tech node - Lu, Sipeng (Nanyang Technological University, 2024)
With the rapid advancement of technology, operational amplifiers (Op-Amps) have evolved into diverse categories, each designed for specific applications and models. The continuous progress in Very-Large-Scale Integration (VLSI) and complementary metal-oxide-semiconductor (CMOS) manufacturing has opened new avenues for optimizing operational amplifier designs. In modern electronics, the demand has shifted towards amplifiers that offer low power consumption, wide bandwidth, high stability, high precision, and reduced production costs. This paper presents the design of an operational amplifier that addresses these demands.